NEGARA KEKELUARGAAN DALAM PERSPEKTIF PANCASILA SILA KE – 3 PERSATUAN INDONESIA - Rijal Bahri Lumban Gaol; Maria Pasmaida Manalu; Siti Tiara Maulia (Cahaya Ilmu Bangsa, 2024)
The long history of Indonesian civilization has experienced various dynamics and enormous pressures. This was based on the position of the Indonesian state which was still under the auspices of the Japanese colony at that time, making the movement of the Indonesian people relatively narrow and difficult to carry out resistance. As time went by, precisely in 1943-1945, the Japanese nation was faced with two powers which were divided into Japan's position in the Second World War and Japan's role in colonization in Indonesia. As a result of this incident, Japan's strength was divided into two, starting with the number of troops, food supplies and weapons of war being categorized as lacking. So Japan was forced to promise independence to Indonesia because there had been so much turmoil caused by Indonesian society, such as rebellions and attacks on Japanese troops. As a result of the promise of independence, Japan and national figures created a body tasked with designing the formulation of independence for the Indonesian nation until on August 17 1945 Indonesia's independence was declared. The independence of the Indonesian nation can be obtained on the basis of a high sense of kinship from every difference in the Indonesian nation, starting from differences in ethnicity, religion, race and class. However, young and old figures never questioned these differences but instead turned these differences into a strength for the Indonesian people to gain independence. However, looking at the sense of family that is currently classified as very low and minimal. This can be seen from the many clashes between tribes and between religious communities. Even though there is already a law that regulates everything regarding actions and activities in the Republic of Indonesia, but if you look at it, the law is only strong in writing but not in its implementation. Differences should be used as wealth for this country, not the cause of the division of this nation.